LIXIVIACIÓN DINÁMICA DE Ni Y Co A PRESIÓN ATMOSFÉRICA DE LATERITA UTILIZANDO ÁCIDO SULFÚRICO Y CÍTRICO CON POSTERIOR PRECIPITACIÓN SELECTIVA / Dinamic Leaching of Ni and Co at Atmospheric Presion of Laterite using Sulphuric and Citric Acid with Later Se - DI YORIO, C.; RANGEL, C.; BETANCOURT, E.; RUS, J. (Revista de la Facultad de Ingeniería UCV, 2006)
El siguiente trabajo se basa en la lixiviación dinámica de lateritas niquelíferas con ácido sulfúrico y cítrico paraextraer por vía hidrometalúrgica: níquel y cobalto. Posterior a la lixiviación, se busca la precipitación selectiva de níquely cobalto en ambas disoluciones ácidas. Al mineral y los precipitados se les caracteriza para saber su morfología ycomposición química mediante difracción de rayos X, microscopía electrónica de barrido y análisis químico cuantitativo.Durante la lixiviación se varía la concentración de los ácidos en 0,5M, 1M y 3M para el ácido sulfúrico; y en 0,1M, 0,2My 0,5M para el ácido cítrico, con una relación de pulpa del 20% en peso y una variación de temperatura entre ambiente de60ºC y 80ºC. Se obtuvo a 80ºC una recuperación de níquel de 73,4% en ácido sulfúrico y de 20,29% en ácido cítrico,mientras que en cobalto se obtuvo 46,29% y 38,88% en sulfúrico y cítrico, respectivamente, en 4 horas. También se probórecircular el licor y la pulpa densa hasta tres veces, donde se llegó a obtener 551,2 mg/l de níquel y 96,3 mg/l de cobaltoen el licor con recuperaciones acumuladas de hasta 40% Ni y 46 % de Co. En los ensayos de precipitación se varia el pHde la solución por medio de la adición de cal a la disolución de ácido sulfúrico, donde alrededor de un pH de 4 ocurre laprecipitación con un 86,45% en níquel y 57,31% en cobalto que precipita; mientras que al licor obtenido por lixiviacióncon ácido cítrico se adiciona vapor de agua y CO2 por separado a fin de desplazar el catión metálico asociado al quelato dela solución lixiviada y conservar el ácido en la solución., donde se obtuvo hasta 48,84% de níquel y 62,06% de cobalto queprecipita.ABSTRACTThe following work studies the dynamic leaching of a nickeliferous laterite with sulphuric and citric acid tohydrometallurgically extract nickel and cobalt. After the leaching process, it was investigated the selective precipitation ofnickel and cobalt in both acid solutions. The laterite ore and the precipitates were characterized to obtain their particlemorphology and chemical composition by means of X rays diffraction, electron microscopy and quantitative chemicalanalysis. During the leaching process, acids concentration were varied from 0.5M, 1M and 3M for the sulphuric acid and0.1M, 0.2M y 0.5M for the citric acid, at a 20% of pulp density and a temperature variation between ambient, 60ºC and80ºC. At 80ºC it was obtained recoveries of nickel of 73.4% in sulphuric acid and 20.29% in citric acid, meanwhile it wasachieved recoveries for cobalt in the order of 46.29% and 38.88 in sulphuric and citric respectively (4 hours leaching).Also it was tested to recirculate the liquor and the leached pulp for three times. It was obtained 551.2 mg/l of nickel and96.3 mg/l of cobalt in the liquor with recoveries up to 40% for Ni and 46% for Co. The precipitation technique was basedin lime addition to the sulphuric acid solution where the pH for precipitation occurs around 4, with 86.45% of the nickeland 57.31% of the cobalt reported in the precipitate; meanwhile in citric solution water steam and CO2 was added separatelyto displace the metallic cation associate to the quelate in the leaching solution, besides to preserve the citric acid in thesolution. The quantity of the nickel and cobalt that precipitate was 48.84% and 62.06% respectively.Keywords: Leaching, precipitation, nickel, cobalt, sulphuric acid, citric acid, chelate.